Early life risk factors of motor, cognitive and language development: A pooled analysis of studies from low/middle-income countries - Sania, Ayesha; Sudfeld, Christopher R.; Danaei, Goodarz; Fink, Günther; McCoy, Dana C.; Hidrobo, Melissa (BMJ, 2019)
Objective: To determine the magnitude of relationships of early life factors with child development in low/middle-income countries (LMICs).